Pengungkapan Emisi Karbon dan Nilai Perusahaan: Bukti Empiris Peran Mediasi Profitabilitas - Ai Sindi Andriani; Jiprian Ramadhansyah; Senny Maulida; Sasa S. Suratman (AKUA: Jurnal Akuntansi dan Keuangan, 2026)
This study aims to examine the effect of carbon emission disclosure on firm value, with profitability serving as a mediating variable, among energy sector companies listed on the Indonesia Stock Exchange (IDX) during the 2022–2024 period. The study is motivated by inconsistent findings in previous research and the limited use of mediation analysis in this context. Using the Partial Least Squares Structural Equation Modeling (PLS-SEM) approach with SmartPLS 4.0, the study analyzes 153 observations from 51 companies selected through purposive sampling. The results reveal that carbon emission disclosure does not have a significant direct effect on firm value but has a significant positive effect on profitability. Profitability, in turn, significantly influences firm value. However, the indirect effect of carbon emission disclosure on firm value through profitability is not significant, indicating that profitability does not act as an effective mediating variable. These findings suggest that investors in the Indonesian capital market still place greater emphasis on financial performance than on carbon emission information when evaluating corporate value.